Effects of water impact on optical properties of metallic mirror samples - Konovalov, V.G.; Solodovchenko, S.I.; Voitsenya, V.S.; Ryzhkov, I.V.; Shtan’, A.F.; Makhov, M.N. (Вопросы атомной науки и техники, 2019)
The effects of exposure in water or water steam on optical properties of mirror samples fabricated of different metals were studied. Materials of samples were: tungsten, beryllium, molybdenum, stainless steel, nickel, copper, rhodium, and amorphous alloys of two compositions. The material of the mirror was found to play a decisive role in degree of impact of water or water vapor on mirror degradation. The most strongly degraded Mo and Cu mirror samples, and the lowest degradation was observed for SS and Rh/SS mirror samples. The reflectance can be restored practically initial level when after water impact procedure the mirrors are exposed to ions of Ar plasma with energy ≥100 eV up to ion fluence >10¹⁹ ion/cm².